Професіограма працівника ювенальної превенції - Костенко, Я. В.; Kostenko, Ya. V. (Право і безпека. – 2017. – № 4 (67). – С.187-192, 2017)
Викладено результати досліджень щодо створення професіограми працівника підрозділів ювенальної превенції в контексті успішного оволодіння професією та подальшого професійного розвитку. Визначено, що професіографічне дослідження є соціально мінливим і мало вивченим напрямком у діяльності працівників поліції, а його розвиток в умовах трансформаційного суспільства є значним внеском у вдосконалення професійної діяльності співробітників поліції, в систему відбору й підбору кадрів. Підкреслено, що успішне реформування правоохоронної системи є неможливим без впровадження нових шляхів і напрямків підвищення результативності процесу відбору й підбору кадрів до ювенальної превенції, одним з яких є комплексна розробка професіограми працівника та моделі відповідності вимогам професії під час прийому на службу, удосконалення методів ефективної та адекватної діагностики особистості.

The author has presented the results of research on the creation of job description of an officer of juvenile prevention unit in the context of successful mastering the profession and further professional development. It has been determined that the job research is socially variable and not enough studied area in the activities of the police, and its development in terms of a transformational society is a significant contribution into improving the professional activities of police officers, into the selection and recruitment system. It has been emphasized that successful reformation of law enforcement system is impossible without implementing new ways and directions of increasing the effectiveness of the selection and recruitment process for juvenile prevention, one of which is the comprehensive development of job description of an officer, the development of a model of compliance with the requirements of the profession at the time of recruitment, improvement of methods of effective and adequate diagnostics of a personality. The suggested in the article theoretical model of job description is the step in bringing the requirements of professional activity of the officers of juvenile prevention units into line with the presence of certain formed psychological properties, processes and entities (knowledge, skills, competences), which will allow to analyze in the future professional and psychological training of such officers to be ready to operate; to detect their compliance with the requirements of the profession, as well as to develop psychological recommendations for psychologists to retrain such officers.

Изложены результаты исследований по созданию профессиограммы работника подразделений ювенальной превенции в контексте успешного овладения профессией и совершенствования в ней. Определено, что профессиографическое исследования – социально изменчивое и малоизученное направление в деятельности сотрудников полиции, а его развитие в современный социальный период является значительным вкладом в совершенствование профессиональной деятельности сотрудников системы внутренних дел, в систему отбора и подбора кадров. Подчеркнуто, что реформирование правоохранительной системы невозможно без внедрения новых путей и направлений повышения результативности процесса отбора и подбора кадров в ювенальной превенции, одним из которых является комплексная разработка профессиограммы работника и модели соответствия требованиям профессии при приеме на службу, совершенствование методов эффективной и адекватной диагностики личности.
Job description of an officer of juvenile prevention
Профессиограмма работника подразделений ювенальной превенции
Костенко, Я. В. Професіограма працівника ювенальної превенції / Я. В. Костенко // Право і безпека. – 2017. – № 4 (67). – С.187-192.
Kostenko, Ya.V. (2017), “Job description of an officer of juvenile prevention” [“Profesiohrama pratsivnyka yuvenalnoi preventsii”], Pravo i Bezpeka, No. 4, pp. 187–192.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; правоохоронні органи; ювенальна превенція; професіограма; психограма; реформування правоохоронної системи; попередження правопорушень; ювенальная превенция; правоохранительные органы; профессиограмма; психограмма; реформирование правоохранительной системы; предупреждение правонарушений; juvenile prevention; job description; psychic profile; reformation of law enforcement system; prevention of offenses